Simulation of magnetic nanoparticles crossing through a simplified blood-brain barrier model for Glioblastoma multiforme treatment. (November 2021) - Gkountas, Apostolos A.; Polychronopoulos, Nickolas D.; Sofiadis, George N.; Karvelas, Evangelos G.; Spyrou, Leonidas A.; Sarris, Ioannis E.
Highlights: Numerical investigation of the MNPs passing through the blood-brain barrier (BBB). A control volume method is used to analyze the flow characteristics into the vessel. The CFD model is validated against in vitro experimental data, showing similar trend. The external magnetic field is the most dominant parameter for the BBB crossing. Abstract: Background and Objectives: Glioblastoma multiforme is considered as one of the most aggressive types of cancer, while various treatment techniques have been proposed. Magnetic nanoparticles (MNPs) loaded with drug and magnetically controlled and targeted to tissues affected by disease, is considered as a possible treatment. However, MNPs are difficult to penetrate the central nervous system and approach the unhealthy tissue, because of the blood-brain barrier (BBB). This study investigates numerically the delivery of magnetic nanoparticles through the barrier driven by normal pressure drop and external gradient magnetic fields, employing a simplified geometrical model, computational fluid dynamics and discrete element method. The goal of the study is to provide information regarding the permeability of the BBB under various conditions like the imposed forces and the shape of the domain, as a preliminary predictive tool. Methods: To achieve that, the three-dimensional Navier-Stokes equations are solved in the margin of a blood vessel along with a discrete model for the MNPs with various acting forces. The numerical results are compared with experimental measurements showing that the model can predict acceptably the flow behavior. Results: The effect of nanoparticles' size, external magnetic field and blood flow in the vessel, on the brain-barrier's permeability are investigated. Three different cases of available area among the endothelial cells per the MNPs' size ratio are also examined, showing that the MNPs' size and available area is not the dominant parameter affecting the permeability of the BBB. The results indicate that the applied magnetic field enhances the drug delivery into the central nervous system (CNS). When larger MNPs (∼100 nm) are exposed to an external magnetic field, the permeability can be improved up to 30%, while it is shown that smaller MNPs (∼10 nm) cannot be driven by the applied magnetic field and in this case the permeability remains relatively unchanged. Finally, the blood flow increase leads to a permeability improvement up to 15%. Conclusions: The applied magnetic field improves up to 45% the permeability of the BBB for MNPs of 100 nm. The geometric characteristics of the endothelial cells, the nanoparticles' size and the blood flow are not so decisive parameters for the drug delivery into the CNS, compared to the external magnetic force.